Ecotheology: Integrating Faith, Creation Care, and Contextual Practice in Indonesian Protestant Congregations - Runtuwene, Hendry Corneles Mamengko (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2025)
Accelerating environmental degradation demands cohesive theological responses, yet current models often treat ecological concerns in isolation. Addressing this gap, the study develops an integrated eco-theological framework for Indonesian Protestant congregations by uniting stewardship theology, cosmotheandric theology, and environmental liberation theology. Employing a multi-method qualitative design, researchers conducted forty semi-structured interviews with clergy, lay leaders, and program participants across four pilot sites; carried out participant observation during eco-liturgy services and community stewardship activities; and systematically analyzed liturgical texts, training curricula, and advocacy reports. Findings reveal that the synthesized framework fosters an eco-spirituality balancing reflective theology on divine–creation interdependence, embodied liturgical practices, and transformative environmental advocacy. Empirical evidence shows strengthened congregational commitment to sustainable initiatives, such as habitat restoration projects and green liturgies, while maintaining theological coherence. This holistic model offers a replicable paradigm for faith communities seeking to integrate deep theological conviction with concrete ecological action.